ICT4Ag: Digital springboard for inclusive agriculture - Hailu, Michael (Technical Centre for Agricultural and Rural Cooperation, 2013)
This issue presents an overview of ICT applications in agriculture on the occasion of the CTA-sponsored conference on ICT4Ag held in Kigali, Rwanda on 4–8 November 2013.